(untitled) (Bangladesh Journal of Medical Science, 2024)
Background Bronchiectasis is a chronic debilitating but neglected pulmonary disease. It is associated with substantial health related burden and health care costs. However, the biochemical parameters related to disease severity have not been sufficiently assessed. Objective: Aim of the present study to find out any association between serum albumin and disease severity of non-cystic fibrosis bronchiectasis. Methods This was a cross-sectional observational study of 33 subjects with non-cystic fibrosis bronchiectasis at department of Respiratory Medicine, National Institute of Diseases of the Chest and Hospital (NIDCH) from December 2019 to March 2021. After taking informed written consent BSI score be calculated and blood was taken for to measure serum albumin. Data was collected through questionnaire. After completion of the data collection, analysis was done with the help of Statistical Package for Social Science (SPSS) version 22. Results Mean age of the study subjects was 43.36 ± 15.65 years with a range of 21 -76 years and more likely to be men (60.6%). History of previous pulmonary tuberculosis found in 48.5% subjects as associated conditions and pseudomonas aeruginosa (21.2%) was the most common organisms in sputum culture. 87.9% of the study subjects had history of exacerbation within last 12 months and 60.6% were hospitalized within last 2 years. More than half (54.6%) of the study subjects had severe, 33.3% had moderate and 12.1% had mild bronchiectasis with the mean BSI score of 9.00 ± 3.05. Mean serum albumin was 3.22 ± 0.84 g/dl. Albumin had a significant negative correlation with BSI score (r = -0.457 and p = 0.008). Conclusion The serum albumin had moderate correlation with disease severity of non-cystic fibrosis bronchiectasis. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1104-1111